Basic Football Game Skills in Extra-Curricular Football Male Students - Anhar, Anhar (Yayasan Insan Mulia Bima, 2024)
This research is a descriptive type of research which aims to determine the basic skills in extra-curricular football at SMPIT Insan Kamil, Bima City. The sample was 51 people. The instrument used in this research is a test. Where only basic skills are tested, such as passing, dribbling test, shooting test. The results achieved in this study were the first, the percentage of passing test scores in the good category was 12 people (23.5%), the medium category was 20 people (39.1%), the poor category was 19 people (37.3%), while the very good category and very poor none (0%). Then the second percentage is test shooting where there are 10 people in the good category (19.6%), 14 people in the medium category (27.4%), 19 people in the poor category. (37.3%), in the very poor category there were 8 people (15.7%), while in the very good category there were none (0%). And the third percentage is the dribbling test where there are 12 people in the good category (23.5%), the average category is 16 people (13.4%), the poor category is 23 people (45.1%), while the very good category is not. yes (0%).